Single-port laparoscopic appendicectomy versus conventional three-port approach for acute appendicitis: A systematic review, meta-analysis and trial sequential analysis of randomised controlled trials. Issue 6 (December 2021) - Zaman, Shafquat; Mohamedahmed, Ali Yasen Y.; Srinivasan, Ananth; Stonelake, Stephen; Sillah, Abdul Karim; Hajibandeh, Shahab; Hajibandeh, Shahin
Abstract: Aims: The aim of this systematic review and meta-analysis is to compare outcomes of single-port laparoscopic appendicectomy (SPLA) and conventional three-port laparoscopic appendicectomy (CLA) in the management of acute appendicitis. Methods: A comprehensive systematic review of randomised controlled trials (RCTs) with subsequent meta-analysis and trial sequential analysis of outcomes were conducted. Post-operative pain at 12-h, cosmesis, need for an additional port(s), operative time, port-site hernia, ileus, surgical site infection (SSI), intra-abdominal collection, length of hospital stay (LOS), readmission, and reoperation were the evaluated outcome parameters. Results: Sixteen RCTs with total number of 2017 patients who underwent SPLA (n = 1009) or CLA (n = 1008) were included. SPLA was associated with a significantly higher cosmetic score (MD 1.11, P= 0.03) but significantly longer operative time (MD 7.08, P = 0.00001) compared to CLA. However, the difference was not significant between SPLA and CLA in the post-operative pain score at 12-h (MD −0.13, P = 0.69), need for additional port(s) (RR0.03, P = 0.07), port-site hernia (RD: 0.00, P = 0.68), ileus (RR 0.74, P = 0.51), SSI (RR 1.38, P = 0.28), post-operative intra-abdominal collection (RR 0.00, P = 0.62), LOS (MD −2.41, P = 0.16), readmission to the hospital (RR 0.45, P = 0.22), and return to theatre (RR 0.00, P = 0.49). Trial sequential analysis demonstrated that the meta-analysis is conclusive for most of the outcomes, except LOS and intra-abdominal collection. Conclusion: Although SPLA is associated with a slightly longer operative time, its efficacy and safety are comparable to CLA in management of uncomplicated appendicitis. Moreover, it offers improved post-operative cosmesis. The available evidence is conclusive, and further trials may not be required. Highlights: Single-port laparoscopic appendicectomy is associated with slightly longer operative time, however, its efficacy and safety are comparable to conventional laparoscopic appendicectomy. Single-port laparoscopic appendicectomy is associated with better cosmetic results. Trial sequential analysis demonstrated that the available evidence is conclusive, and further trials may not be required.